Direct and interactive effect of evaluation period on managerial time orientation (Revista de Administração, 2013)
The aim of this paper is to investigate the direct and interactive effect of evaluation periods on managerial time orientation (MTO), the time horizon between resource allocation and its financial effect. Based on accounting and economics literature, we examine the following hypotheses: i) a longer evaluation period positively affects MTO; and ii) the positive effect of a longer evaluation period on MTO is higher in cases where nonfinancial measurements are given greater relative importance than financial measurements. Based on partial least-squares analysis, we test the hypothesis using survey data from 66 middle-level managers in 11 organizations. Our results suggest that the evaluation period does not have a direct effect on MTO; however, by considering its interaction with performance measurement, the results indicate that the effect of the evaluation period on MTO depends on the relative importance of financial versus nonfinancial measurements. The main implication of these results is that the use of a longer evaluation period, along with greater importance of nonfinancial measurements, does not positively affect MTO; on the contrary, this positive effect on MTO is present when a shorter evaluation period is associated with a lower importance of nonfinancial measurements.